Perbandingan Tingkat Efisiensi OPZ Sebelum dan Saat Pandemi di Indonesia - Ulfi Sasabel Chumairoh; Lina Nugraha Rani (Institut Agama Islam Negeri Palopo, 2022)
This study aims to compare the level of efficiency of OPZ before and during the pandemic. This research is a quantitative research with the output-oriented Data Envelopment Analysis (DEA) method. The DEA approach used is the production approach. The input variables used include the total cost of amil salaries, total socialization costs and total operational costs. While the output variables include the amount of funds collected and the amount of funds channeled. The type of data used is secondary data originating from financial reports in 2019 and 2020. The sampling technique that the author uses is Purposive Sampling, which takes 9 national-level OPZs consisting of BAZNAS, LMI, Dompet Dhuafa, Rumah Zakat, Orphanage and Zakat. , Indonesian Islamic Da'wah Council, Arrahman Indonesia Orphanage House, Darul Qur'an Nusantara and LAZISNU. The results show that on average, the OPZ efficiency value in 2019 was 0.74 and in 2020 it was 0.70. This trend indicates that there is a decrease in efficiency in the OPZ. it can be concluded that there is no significant difference in the results of OPZ efficiency before the pandemic and during the pandemic. There are 4 OPZs that experience continuous efficiency in 2019 and 2020. Meanwhile, the other five OPZs have yet to experience efficiency. The results of this study can be used as a reference and consideration for policy making in OPZ and relevant institutions/work